BEYOND BORDERS: UNVEILING THE MEDIA REPRESENTATION OF ZUZANA ČAPUTOVÁ IN CZECH ONLINE NEWS - Švecová, Martina (Communication Today, 2024)
This study underscores the influential capacity of transborder media communication in transcending geographical and political barriers, profoundly influencing political inclinations, voter behaviour, and public sentiment in neighbouring countries. The study specifically evaluates the portrayal of Zuzana Čaputová in Czech online media. Transborder communication between linguistically similar nations can result in distinctive representations of political figures from adjacent countries. Therefore, analysing this communication is crucial for comprehending the dynamics between Slovakia and the Czech Republic. It also contributes to a broader understanding of transregional media narratives in Central and Eastern Europe. The research identified various thematic lines in the media representation of Čaputová, including comparison, fashion, personality, values, expertise, and a line of defenders, where commentators counteract hoaxes. Additionally, the study acknowledges that media framing is not gender-neutral and examines transborder communication from this perspective. The discussion provides a comprehensive overview of Čaputová’s media representation and her perceived role in the public and political spheres.